Resolución de problemas y el aprendizaje de la matemática en niños de la Institución Educativa Inicial N°728, Caballococha 2024 - Pereyra Pezo, Meredith (2024)
The purpose of this research was to determine the relationship between the level of problem solving and the level of mathematics learning in children from the Institution Educative Initial N°728, Caballo Cocha 2024. This study used a quantitative research approach. This is relational research with a correlational and transactional design. This design focuses on describing the relationships between two or more variables at a specific time, measuring how the variables correlate. The population under study was made up of all the children of the Initial Educational Institution No. 728, Caballo Cocha 2024, with a total of 118 children. Observation was used as an evaluation technique and instrument, and an observation guide was used as an instrument for data collection, which was validated by a team of experts in the field. The results showed that a correlation coefficient of 0.715 was obtained between problem solving and mathematics learning, with a significance level of 0.05. Concluding, there is a significant relationship between the level of problem solving and the level of mathematics learning in children.